On local fractional Volterra integral equations in fractal heat transfer - Wu Zhong-Hua (Thermal Science, 2016)
In the article, the fractal heat-transfer models are described by the local fractional integral equations. The local fractional linear and nonlinear Volterra integral equations are employed to present the heat transfer problems in fractal media. The local fractional integral equations are derived from the Fourier law in fractal media.